Writing India anew : Indian-English fiction 2000-2010 - Sen, Krishna; Roy, Rituparna (ICAS publication series. Edited volumes, 2013)
An assessment of twenty-first-century Indian-English fiction, 'Writing India Anew' features fifteen essays by some of the most prominent scholars in the field and explores a range of themes, including the remapping of mythology and history, the reassessment of globalized India, and technical experimentation in the epic, science fiction, and the graphic novel. Ultimately, the contributors to this volume contend that the current body of work in Indian-English fiction is so varied and vibrant that it can no longer be dismissed as derivative or dispossessed, or even as mere postcolonial 'writing back' or compensatory national allegory.